1992
DOI: 10.1073/pnas.89.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of cytoplasmic mRNA-binding proteins of Xenopus oocytes identifies a family of RNA-binding proteins.

Abstract: Storage of maternal mRNAs as nontranslated ribonucleoprotein (RNP) complexes is an adaptive strategy in various vertebrate and invertebrate oocytes, for rapid translational recruitment during embryonic development. Previously, we showed that Xenopus laevis oocytes have a soluble cytoplasmic pool of mRNA-binding proteins and particles competent for messenger RNP assembly in vitro. Here we report the isolation of cDNAs for the most abundant messenger RNPs, the 54-and 56-kDa polypeptide (p54/p56) components of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(95 citation statements)
references
References 55 publications
(42 reference statements)
3
92
0
Order By: Relevance
“…We have also reported that microinjection with Xoom antisense RNA causes inhibition of the epibolic cell elongation in the outer ectodermal layer through disorganization of F-actin without any disruption to mesodermal gene expression (Hasegawa & Kinoshita 2000). The (Murray et al 1992;Goodman et al 1998;Lieb et al 1998;Stennard et al 1999 (Hasegawa et al 1999).…”
Section: Discussionmentioning
confidence: 93%
“…We have also reported that microinjection with Xoom antisense RNA causes inhibition of the epibolic cell elongation in the outer ectodermal layer through disorganization of F-actin without any disruption to mesodermal gene expression (Hasegawa & Kinoshita 2000). The (Murray et al 1992;Goodman et al 1998;Lieb et al 1998;Stennard et al 1999 (Hasegawa et al 1999).…”
Section: Discussionmentioning
confidence: 93%
“…The chicken YB-1, subsequently cloned, also showed DNA binding with little dependence on the presence of a Y/CCAAT box. 64 (ii) The Xenopus FRG-1 gene was cloned with expression libraries 67 probed with antibodies directed against p54/p56, 68 one of the subunits of the mRNAbinding complex biochemically identified in the 1970s, and widely studied for its role in mRNA translation. 68 Thereafter, research on YB-1 proceeded, by and large, in two parallel fields: its role in the control of mRNA biology (splicing, stability, translation), in which it has taken a center-stage position (Bouvet and Wolffe 69 ; reviewed in Evdokimova et al 70 ), and its role in the control of transcriptional initiation, which has been more controversial.…”
Section: Y and Ccaat: Two Names One Entitymentioning
confidence: 99%
“…In addition to the CCAAT element, YB-1 also binds to several unrelated sequences as well as single-strand DNA and mRNA (47)(48)(49)(50)(51)(52)(53). There are many precedents for the ability of a DNA-binding protein to recognize unrelated sequences (54)(55)(56).…”
Section: And Class II Mhc Genes (33) Ifn-"(-induced Li Gene Transcmentioning
confidence: 99%